PRACTICAL APPLICATIONS OF HASH FUNCTIONS MD5, SHA-1, AND SHA-256 USING VARIOUS SOFTWARE TOOLS TO VERIFY THE INTEGRITY OF FILES: PRACTICAL APPLICATIONS OF HASH FUNCTIONS MD5, SHA-1, AND SHA-256 USING VARIOUS SOFTWARE TOOLS TO VERIFY THE INTEGRITY OF FILES - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
In this scientific paper hash functions such as MD5, SHA-1, and SHA-256 are widely utilized in the field of cryptography to verify file integrity, confirming that files remain unaltered and free from corruption. The practical application of the hash functions MD5, SHA-1, AND SHA-256 through five widely used software tools: 7z, PowerShell, BullZip MD5 Calculator, HashCalc and CrypTool 1.4.40 is made. The analysis focuses on each tool's effectiveness in calculating and comparing hash values, emphasizing their strengths and weaknesses in ensuring data integrity. By investigating the functionality and applications of each tool, this scientific study provides important perspectives on the practical significance of MD5, SHA-1, and SHA-256 for maintaining the authenticity and reliability of digital files.